The Analysis of Video Conference With ITU Standarization (International Telecommunication Union) That Joining in Inherent At Bandar Lampung University - Happy Reksa; Maria Shusanti Febrianti (Bandar Lampung University (UBL), 2013)
Video conference is an interactive communication device that allows two or more persons can be different in the location can interact through two-way transmission of audio and visio. For doing this video video conference must be standarded with ITU(international Telecommunication Union) so that communication car run as what we want. Video conference has been widely used in life. For example bussiness, education, military, and other purposes in long distance. In education, video conferencing can be done for long distance education, video conferencing can be used for meetings with other universities in another town. That’s why Bandar Lampung University joining in Inherent (Indonesia Higher Education Network) to attend conference video. Inherent network is a closed communication network between universities in Indonesia. To be able to conference, it is a facility obtained from inherent grant in 2007 by the directorate of higher education. This study was conducted to measure the suitability of polycom VSX 7000 video conference with standard ITU (international telecommunication union).